Antibacterial and antibiofilm properties of Phlomis and Stachys species (Bangladesh Journal of Botany, 2020)
The ethyl acetate and methanol extracts of Phlomis pungens var. pungens, P. nissolii, P. armeniaca and Stachys byzantina, S. cretica L. subsp. mersiaea and S. cretica L. subsp. Smyrnaea were evaluated for their antibacterial and antibiofilm activities. Five bacterial species were used are Bacillus subtilis, Pseudomonas aeruginosa, Shigella sonnei, Salmonella typhimurium and Yersinia enterocolitica. The ethyl acetate and methanol extracts of plant species showed good antibacterial activity against all bacterial strains. More significantly, ethylacetate and methanol extracts of all Phlomis species were found to be more effective on degredation of mature biofilm against all used bacterial strains than extracts of Stachys species. The findings of the present study highlight the promising role of Phlomis and Stachys extracts as new lead structures in the search for novel antibacterial and antibiofilm agents.